Islamic Republic of Afghanistan : Technical Assistance Report-Report on the External Sector Statistics Mission (March 12-22, 2018). (IMF Staff Country Reports; Country Report ;, 2018)
A technical assistance (TA) mission on external sector statistics (ESS) was conducted in Beirut, Lebanon, during March 12-22, 2018, for the Da Afghanistan Bank (DAB).1 The mission took place at the request of the DAB and with strong support of the IMF's Middle East and Central Asia Department. This mission is part of the Middle East Regional Technical Assistance Center (METAC) work program. The main objectives of the mission were to assist the DAB in improving the quality of the balance of payments and International Investment Position (IIP) by suggesting improvements in the statistical techniques and promoting the use of adequate source data. The main focus of the mission was on filling data gaps by developing new estimation methods based on existing and new data sources.